93-(4m-8)=53

Simple and best practice solution for 93-(4m-8)=53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 93-(4m-8)=53 equation:


Simplifying
93 + -1(4m + -8) = 53

Reorder the terms:
93 + -1(-8 + 4m) = 53
93 + (-8 * -1 + 4m * -1) = 53
93 + (8 + -4m) = 53

Combine like terms: 93 + 8 = 101
101 + -4m = 53

Solving
101 + -4m = 53

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-101' to each side of the equation.
101 + -101 + -4m = 53 + -101

Combine like terms: 101 + -101 = 0
0 + -4m = 53 + -101
-4m = 53 + -101

Combine like terms: 53 + -101 = -48
-4m = -48

Divide each side by '-4'.
m = 12

Simplifying
m = 12

See similar equations:

| 2(3c)=36 | | f=(12)60-2/3r | | X*2+x*2=-14-3 | | -200x-2500=5100 | | -124=-4v-2(6+6v) | | -4x-18=73 | | y=x/2-13^3 | | 5-w+11=51 | | 7+7(7n-8)=98 | | 6x-(3x+7)=27 | | 2x+29=300 | | 6n^2+48n+72=0 | | 28n^2=-96-183n | | 5a+56=(7)(8) | | 10x^2y= | | n(3)=n+12 | | 3x+4x=16-3x | | 4c/5=4 | | 3x^2+8x^2-15x-40=0 | | 6(x+5)-42=8 | | 33xy^5z^3= | | h=16t^2+400t | | 8(x+2)=(6x-7) | | sinx+cosx=6x | | 15(x+1)-5(10x+9)+2(5x+3)+4=0 | | 7z-9=3 | | 4/3=10/x | | -4p=44 | | 11-a=13 | | 2x+14=-28 | | 6(-6x+4)=-8(4x-6) | | -x-13+25=-3+52 |

Equations solver categories